Determination and comparison of pulmonary volumes between populations living at the sea level and more than 3000 msnm - Mauricio Canaviri, Vasthy (2018)
ABSTRACT Objective: To determine the percentage of lung volumes and capacities of the inhabitants of Huancayo that live at sea level and to verify if the normality curves of NAHNES III MEXICANO-AMERICANO conform to our population group. Methods: A calibrated MIR SPIROBANK digital spirometer was used, a non-probabilistic sampling was carried out, for convenience, with a population sample of 400 inhabitants comparable by size, age and sex, divided into 2 groups. Results: Men and women living at 3,000 meters above sea level have 13.5% and 14% respectively more FORCED LIFE CAPACITY (CVF), than those living at sea level. Men and women living at more than 3,000 meters above sea level have 12.6% and 14% respectively more FORCED SPIRITUAL VOLUME IN THE FIRST SECOND (VEF 1) than those living at sea level. Men and women living at 3000 meters above sea level have 88.32% and 88.74% of FEV1 / CFV, while men and women living at sea level have 89.55% and 89.5% of FEV1 / CFV. similar with the THEORETICAL VALUES OF NHANES III MEXICANAMERICAN 84,7% and 87% for men and women.Conclusion: The inhabitant of height has FVC and FEV 1 greater than the population that resides at sea level, however the FEV1 / FVC ratio has similar percentages without significant statistical difference. Key words: Height inhabitant; CVF; FEV1; Spirometry; NHANES III. (source: MeSH NLM) DOI: 10.25176/RFMH.v18.n3.1592